PERANCANGAN, PEMBUATAN DAN PENGUJIAN SISTEM KENDALI TANGKI GANDA UNTUK ALAT PERAGA KULIAH SISTEM KENDALI - Abidin, Zainal; Maryanto, Is; Sutikno, Priyono (Mesin, 1996)
This paper describes the motivation and design criteria for the development of a couple-tank control system which is intended to be used as a demonstration apparatus for a lecture course on Introduction to Control Systems. The work also demonstrates the performances of the controlled system in tracking various types of command inputs, Control strategies implemented to the system are On-Off control, Proportional control and Proportional-Integral control. Inï¬uences of dynamic interaction between channels on the performance degradation are also shown in this work. Except as a control system design example, this work is expected to be useful to mechanical engineering lecturers giving courses on Introduction to Control Systems, particularly to those in private universities.